Exciton dynamics : ultrafast exciton dynamics and two-photon pumped lasing from ZnSe nanowires - Xing, Guichuan (2014)
The commonly accepted paradigm that the higher pump intensities needed for two photon excitation (TPE) correspond to a higher exciton density threshold for two-photon pumped lasing (nth) is re-examined by T.-C. Sum and co-workers using femtosecond time-resolved spectroscopy. The results on page 319 show that a much lower nth is needed to achieve lasing in single ZnSe nanowires with TPE compared to single photon excitation (SPE). This finding has significant implications for the photostability and durability of nanowire lasing.